2011
DOI: 10.1002/ecj.10311
|View full text |Cite
|
Sign up to set email alerts
|

Brain activity when reading sentences and emoticons: an fMRI study of verbal and nonverbal communication

Abstract: SUMMARYIn this paper, we describe a person's brain activity when he or she sees an emoticon at the end of a sentence. An emoticon consists of some characters that resemble the human face and expresses the sender's emotions. With the help of a computer network, we use e-mail, messaging, avatars, and so on, in order to communicate with a recipient. Moreover, we send an emotional expression by using an emoticon at the end of a sentence. In this research, we investigate the effect of an emoticon as nonverbal infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
4
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 11 publications
1
36
4
2
Order By: Relevance
“…The emotions tied to facial expressions should also be easier to spot (GANSTER et al, 2012, p. 229). In this sense, Yuasa et al (2011) showed how these graphic emoticons activate the area used in emotional discrimination and also the area that is typically activated when seeing a human face, although to a lesser degree. Finally, the eventual relevance of the overall message (verbal content plus emoticon) should also increase due to a lowering of mental effort needed to ascribe meaning to the graphic emoticon.…”
Section: Iconicitymentioning
confidence: 97%
“…The emotions tied to facial expressions should also be easier to spot (GANSTER et al, 2012, p. 229). In this sense, Yuasa et al (2011) showed how these graphic emoticons activate the area used in emotional discrimination and also the area that is typically activated when seeing a human face, although to a lesser degree. Finally, the eventual relevance of the overall message (verbal content plus emoticon) should also increase due to a lowering of mental effort needed to ascribe meaning to the graphic emoticon.…”
Section: Iconicitymentioning
confidence: 97%
“…It remains then to see if this conscious effect is replicated in more unconscious behavioural measures, such as facial and neural response. Yuasa, Saito, and Mukawa (2011b) address the question of neural response. They used fMRI to localize the neural activity of subjects viewing verbal statements accompanied by sentence final textual emoticons.…”
Section: Perception Of Emoticonsmentioning
confidence: 99%
“…Researchers suggest that emoticons fill the gap left by facial expression (Rezabek & Cochenour, 1998;Thompson & Foulger, 1996). The fMRI research of Yuasa, Saito, and Mukawa (2011b), in contrast, finds that viewing ASCII (American Standard Code for Information Interchange) emoticons (e.g., :), :( ) does not activate the same parts of the brain as does viewing facial expressions. In the current study, an online survey was conducted to investigate the effects of emoticons on perception of ambiguous sentences and users' beliefs about the effects of and reasons for emoticon use.…”
mentioning
confidence: 99%
“…These findings suggest that these kinds of emoticons may be associated with emotional discrimination. In a posterior study, Yuasa et al (2011) investigated brain activations during the exposure to emoticons presented after sentences. Results showed that emoticons are associated with nonverbal information processing and that the brain areas involved in verbal and nonverbal information processing are more active when sentences are followed by emoticons than when they are not.…”
Section: What Does Neuroscience Tell Us About Emoticons?mentioning
confidence: 99%